Over-Expression of MicroRNA-210 and MicroRNA-185-5p in Normotensive Late-Fetal Growth Restriction: Preliminary Cohort Study - Esra Altan Erbilen; Gulizar Fusun Varol; Necdet Sut; Nebiye Pelin Turker; Niyazi Cenk Sayin (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Late Fetal Growth Restriction (LFGR), a condition associated with perinatal and long-term neurodevelopmental problems, is caused by inadequate placental transfer of oxygen and nutrients to the fetus. This preliminary study evaluates the expression profiles and clinical significance of hypoxia-sensitive microRNA-210 (miR-210) and microRNA-185-5p (miR-185-5p) in placental and maternal circulation. The potential clinical implications of this research could significantly enhance the management of LFGR.